2020
DOI: 10.36376/bmj.v7i2.140
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Coma Scale (GCS) dan Tekanan Darah Sistolik Sebagai Prediktor Outcome Pasien Cedera Kepala

Abstract: Dikarenakan angka kematian pasien cedera kepala tinggi, sehingga diperlukan penilaian awal yang akurat untuk memprediksi hasil dan asuhan keperawatan yang sesuai dengan kondisi pasien. Tujuan penelitian ini adalah untuk mengetahui GCS, tekanan darah sistolik, dan frekuensi pernapasan yang dapat menjadi prediktor mortalitas pasien cedera kepala di RSUP Haji Adam Malik Medan. Desain penelitian ini adalah observasional analitik dengan pendekatan retrospektif. Populasi dalam penelitian ini adalah rekam medis pasie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…This is in accordance with research conducted by Khairunnisa in 2020 at ZAH which showed that a normal CT scan of the head or cerebral edema could be found in head injury patients. 19 The present study show that there is a possibility that patients will experience diffuse edema lesions due to head injury even without focal lesions of intracranial hemorrhage. This is in accordance with the theory that the pathophysiology underlying cerebral edema is neuroinflammation which can cause damage to the blood brain barrier (BBB) in the first 24 hours after head injury.…”
Section: Discussionmentioning
confidence: 50%
“…This is in accordance with research conducted by Khairunnisa in 2020 at ZAH which showed that a normal CT scan of the head or cerebral edema could be found in head injury patients. 19 The present study show that there is a possibility that patients will experience diffuse edema lesions due to head injury even without focal lesions of intracranial hemorrhage. This is in accordance with the theory that the pathophysiology underlying cerebral edema is neuroinflammation which can cause damage to the blood brain barrier (BBB) in the first 24 hours after head injury.…”
Section: Discussionmentioning
confidence: 50%
“…Cedera kepala didefinisikan sebagai suatu cedera yang terjadi pada kulit kepala, otak, hingga tengkorak yang diakibatkan oleh suatu benturan, pukulan atau sentakan di kepala atau cedera kepala yang tembus sehingga dapat menyebabkan gangguan trauma fungsi otak yang disertai atau tidak di sertai darah interstitial di dalam substansi otak yang di ikuti putusnya kontiunitas otak [2]. Kasus cedera kepala semakin bertambah dikarenakan berkembangnya alat transportasi kendaraan bermotor yang menyebabkan penggunaannya pun semakin melonjak tinggi, baik di negara-negara maju maupun di negara-negara berkembang [3]. Setiap tahunnya, lebih dari satu juta orang di dunia meninggal karena cedera kepala yang terjadi akibat kecelakaan lalu lintas dan jutaan lainnya menderita kecacatan permanen [4].…”
Section: Pendahuluanunclassified
“…The lowest total score is 3 and the highest score is 15. GCS score for classifying head injuries is divided into mild (GCS 13-15), moderate (GCS 9-12), and severe (GCS 3-8) categories (Marbun et al, 2020;Dixon et al, 2020 ;Salottolo et al, 2021;Ginting, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%